A ANALISIS STRATEGI PUBLIC RELATION LINGKAR GANJA NUSANTARA DALAM MEMBENTUK PERSEPSI GANJA SEBAGAI PENGOBATAN ALTERNATIF: STRATEGI PUBLIC RELATION LINGKAR GANJA NUSANTARA DALAM MEMBENTUK PERSEPSI GANJA - Wicaksono, Aditya; Leonardi, Aska (FISIP UPNVJ, 2023)
Lingkar Ganja Nusantara or commonly known as LGN has Public Relations which aims to shape the perception of cannabis as an alternative medicine through Instagram social media. In forming the perception of cannabis as an alternative medicine, LGN saw difficulties in educating or informing literacy about cannabis plants in Indonesia, with the perception of the public that viewing cannabis as haram and having no benefits. But LGN invites regional or regional nodes to take part in spreading content on Instagram through the @lgn_id account, by trying to provide information about cannabis both in alternative medicine information and up to the history of cannabis itself. The research objectives are as follows, to determine the public relations strategy of Lingkar Ganja Nusantara in shaping the perception of cannabis as an alternative medicine. The method used is descriptive qualitative method, where the research subjects consist of 1 key informant and 4 informants. Data collection techniques were carried out through in-depth interviews, literature studies, documentation. The data analysis technique used in this study is the Miles and Huberman Model data analysis technique. The result of this study is the Public Relations of Lingkar Ganja Nusantara by looking at the public relations campaign strategy through The Nine Steps of Strategic Public Relations model. This is in accordance with the goal of the Maritime Maritime Maritime Circle of Public Relations, which is to shape the perception of cannabis as an alternative medicine.